Location‐assisted clustering and scheduling for coordinated homogeneous and heterogeneous cellular networks. Issue 1 (26th November 2012) - Eslami, Mohsen; Elliott, Robert C.; Krzymień, Witold A.; Al‐Shalash, Mazin; Dammann, Armin; Plass, Simon; Fazel, Khaled
ABSTRACT The multiple‐input multiple‐output (MIMO) downlink with transmitter coordination in a cellular network is considered. The transmitters are assumed to be either neighbouring base stations (homogeneous) or a base station with a number of remote radio heads that form picocells in its coverage area (heterogeneous). In centralized coordinated transmission from a cluster of nodes, the channel state information (CSI) of users needs to be sent to a central processor for precoding and resource allocation. Real‐time CSI feedback from the users to their home base station and from the base stations to the central processor is a serious challenge from a practical point of view. In this work, efficient location‐assisted limited‐feedback schemes for homogeneous and heterogeneous cellular networks are proposed. First, a hybrid mode transmission scheme with reduced feedback requirement is proposed for a homogeneous network, in which on the basis of the location of users, some are served using a single‐cell multiuser MIMO approach and some using a network MIMO approach. Next, for a heterogeneous network, a location‐assisted clustering and scheduling scheme is proposed for the case of joint reference signals, in which multiple transmission nodes that share the reference signals cannot be distinguished from each other. We evaluate the performance of our schemes with a series of simulations. In the homogeneous scenario, we compare with the case of full CSI, and in the heterogeneous scenario, we compare with joint transmission from all nodes in a cell. Copyright © 2012 John Wiley & Sons, Ltd.